Parent Parenting with Aggressiveness - Nuzliah Jamaluddin; Juli Andriyani (Jurnal Counseling Care, 2019)
The background of the research is the use of parenting that is wrong from parents to children. The purpose of this research is to look at the relationship between parenting parents and the aggressiveness of students. This type of research is quantitative with a correlation approach. The sample in this study was 32 students and data collection techniques using a questionnaire and data analysis techniques using correlation analysis. Based on the analysis of the data it was revealed that 1) the aggressiveness of students in SMA Negeri 2 Indra Jaya was in the high group with a percentage of 43.7%, while the level of parenting (authoritarian) with a percentage of 40%, there was a significant relationship between parenting parents with aggressiveness students namely 0.608 with a strong correlation r value